Deciding what to do with your life - Yoskovitz, Benjamin; Croll, Alistair (O'Reilly Media, Inc., 2016)
Two key factors in building a business involve determining its viability in the market, and whether YOU want to do it. Understand what these factors are and how to analyze a business idea and your desire to pursue it. Why is it important? Too many entrepreneurs spend time pursuing ideas that don't have a market. Entrepreneurs need to understand what problems the idea solves, who your customers are, and what the potential costs and revenues are. You also need to evaluate your desire and ability to execute on the idea, and whether you'll enjoy it. What you'll learn--and how you can apply it You'll learn how to apply the Lean Canvas created by Ash Maurya to quickly develop a one-page business plan that can help you evaluate the viability of a business idea or project. You'll also learn three important questions to ask about how YOU feel about your project or idea and your ability to execute on it. This lesson is for you because ... You're an entrepreneur looking for methodologies to quickly evaluate your ideas You want to become an entrepreneur but aren't sure if the idea you have is viable You have a business idea but aren't sure how to evaluate it in a personal and market context Prerequisites None Materials or downloads needed in advance None This lesson is take from Lean Analytics by Alistair Croll and Benjamin Yoskovitz.